2021
DOI: 10.1186/s13578-021-00703-4
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine facilitates HIV infection of primary human monocytes through inhibiting cellular viral restriction factors

Abstract: Background Methamphetamine (METH), a potent addictive psychostimulant, is highly prevalent in HIV-infected individuals. Clinically, METH use is implicated in alteration of immune system and increase of HIV spread/replication. Therefore, it is of importance to examine whether METH has direct effect on HIV infection of monocytes, the major target and reservoir cells for the virus. Results METH-treated monocytes were more susceptible to HIV infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
(62 reference statements)
2
3
0
Order By: Relevance
“…Gene expression analyses of human macrophages treated with meth could determine the transcriptional pathways that meth alters to mediate differential protein expression. In vivo studies of gene expression in SIV-infected macaque brains exposed to meth found an increased proportion of infected macrophages, which is consistent with our mass spectrometry data and prior in vitro studies [ 92 , 93 ]. These analyses demonstrated the differential expression of genes in the complement pathway and electron transport chain function [ 93 ].…”
Section: Discussionsupporting
confidence: 92%
“…Gene expression analyses of human macrophages treated with meth could determine the transcriptional pathways that meth alters to mediate differential protein expression. In vivo studies of gene expression in SIV-infected macaque brains exposed to meth found an increased proportion of infected macrophages, which is consistent with our mass spectrometry data and prior in vitro studies [ 92 , 93 ]. These analyses demonstrated the differential expression of genes in the complement pathway and electron transport chain function [ 93 ].…”
Section: Discussionsupporting
confidence: 92%
“…Meth increased the amount of HIV released from cells from each independent donor ( Supplementary Figure 2 ). This is consistent with other studies that reported increased HIV infection in other cell types including macrophages ( 46 , 47 ).…”
Section: Resultssupporting
confidence: 93%
“…Similarly, the use of methamphetamine via IDU or “booty bumping” can result in HIV infection through direct inoculation of the bloodstream from a shared needle or damage the rectal mucosa, which increases biological susceptibility to HIV infection if exposed during condomless receptive anal sex ( Cantrell et al, 2006 ). Methamphetamine also directly alters cellular processes, resulting in decreased intracellular immunity to HIV and greater HIV replication in human monocyte cells ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%